Copper Deficiency and Evaluation in Infants Requiring Long-term Parenteral Nutrition - Kim, Yujin; Shin, Hyun Jung; Bae, Hye Jung; Choi, Nigh; Cho, Eun Jung; Cho, Yoon Sook; Shin, Seung Han; Kim, Ee-Kyung; Kim, Han-Suk (Journal of Korean Society of Health-System Pharmacists, 2021)
Background : Long-term parenteral nutrition (PN) can increase the risk of copper deficiency. This study aimed to analyze the incidence and risk factors associated with copper deficiency in infants requiring long-term PN and to evaluate the adequacy of intravenous (IV) copper supplementation. Methods : This was a retrospective study of infants who were admitted to the neonatal intensive care unit (NICU) of a tertiary hospital in Korea from July of 2015 to June of 2020, had their serum copper concentration measured, and received PN for more than two weeks. Patients who were supplemented with IV copper and whose serum copper concentration was monitored after administration were placed in a subgroup to evaluate the copper supplementation. Results : Of the 63 patients, 39 (61.9%) were deficient in copper (serum Cu <70 μg/dL). In the copper deficiency group, gestational age and birth weight were significantly lower, and the proportion of premature infants and extremely low-birth-weight infants were significantly higher. Gestational age of less than 32 weeks was an independent risk factor for copper deficiency. In the copper deficiency group, the total NICU stay was longer, absolute neutrophil count, hemoglobin, and platelet levels were lower, and the proportion of bronchopulmonary dysplasia and rickets was higher. Conclusion : Copper deficiency was common in infants receiving long-term PN without copper, especially in patients of young gestational age. Adequate copper supplements are recommended to prevent the clinical consequences of copper deficiency. It is necessary to develop single-entity products of IV copper or multi-trace element products suitable for infants. KCI Citation Count: 0